ANALISIS KESULITAN MEMBACA TEKS BACAAN PADA SISWA SMK KRISTEN IMMANUEL II - Setiany, Venny; Veronica, Tjen; Khiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
Reading is one of the most important components of Chinese language courses. Some people consider reading to be a difficult subject, especially for students who do not have a foundational knowledge of Chinese. During the learning process, they often encounter various difficulties. In order to identify the reasons behind students"™ reading difficulties, the author conducted a study involving first-year Accounting students at Emmanuel Vocational School. The aim of this study is to understand the reading comprehension abilities of first-year students at Emmanuel Vocational School and to identify the difficulties they face in reading Chinese texts. This study employed a quantitative research method. The data collection instruments included a questionnaire with 20 items, an interview with Chinese language teachers consisting of 5 questions, and a reading test with 20 items.The author concludes that students face four main types of reading difficulties: vocabulary difficulties, grammatical difficulties, content comprehension difficulties, and text structure difficulties. When reading texts, many students do not recognize numerous Chinese characters. Their lack of vocabulary knowledge makes it hard for them to understand the meaning of the texts. The research results indicate that first-year students at Emmanuel Vocational School still face challenges in reading Chinese texts, and their reading abilities need further improvement.